CIRI-CIRI MAKNA IDEASIONAL DALAM IKLAN PERAWATAN KULIT MS GLOW UNTUK WANITA - simatupang, Assyifa Dara Humairah (Universitas Harapan Medan, 2025)
This study aims to reveal the existence of ideational meanings contained in MS GLOW skin care product advertisements where the existence of these meanings can influence women's way of thinking and persuade them to buy the product.The researcher here collects the data related to the study by capturing on Ms Glow website.The theory used in this research is transitive theory.The ideational meaning is obtained from the transitivity system analysis.There are six processes that appear in MS Glow skin care product advertisements which consist of material, relational and mental processes.The most dominant process that appears is the material in which the process is used to represent women's products and attitudes.